Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 45118 species occurrences available in GBIF matching the query: { "and" : [ "Geometry POLYGON((19.51931 39.73820,96.95095 39.73820,96.95095 70.76359,19.51931 70.76359,19.51931 39.73820))", "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", "TaxonKey is Reptilia", "Year 1962-2021" ] } The dataset includes 45118 records from 108 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0044646-210914110416597/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences